Analisis Penerapan Direct Marketing guna Meningkatkan Penjualan Produk pada Anna Art Gallery - Sampir Andrean Sukoco; Adilla Septiananda Fanani (Majalah Ilmiah DIAN ILMU, 2022)
Direct marketing is a marketing method that is commonly applied by some business people because it has an effective effect on increasing product sales. This research uses a qualitative method with a case study at Anna Art Gallery. Researchers used purposive techniques to determine informants. In this study, three informants were selected. Data collection is done through observation, interviews, and documentation. Anna Art Gallery's business is engaged in selling art products and services, including handicrafts for wedding purposes such as wedding dowries, offerings, wedding souvenirs, wall decorations, various bouquets and also various gifts. As an effort to increase product sales, Anna Art Gallery implements direct marketing as its strategy. Some of the direct marketing used includes face-to-face sales, telemarketing, online marketing, and the use of catalogs. This method has succeeded in making the Anna Art Gallery business have good sales, so that the business continues to grow and develop.